Analisis Perbandingan Sistem Pendukung Keputusan Menggunakan Metode SAW dan WP Dalam Penilaian Kinerja Tenaga Kontrak - Yusril Yusuf; Lukman Bachtiar (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
Employees at the Regional Secretariat office of East Kotawaringin Regency are divided into 2, namely Permanent Employees (Civil Employees) and Contract Employees (Contract Workers). Contract workers are employees who have non-permanent employment status, so it is necessary to evaluate the quality of their performance to determine the sustainability of the contract extension. There are 6 assessment criteria that are used as a reference for assessing the performance of contract workers, namely Individual Performance Targets, Service Orientation, Integrity, Commitment, Discipline, and Cooperation. The performance appraisal of contract workers at SETDA Kotim has been computerized, but there is still no method applied to the performance appraisal of contract workers, causing the performance appraisal of contract workers to be unstructured. From these problems, a decision support system is needed to be able to assist the process of assessing the performance of contract workers. The researcher conducted a comparative analysis between the SAW method and the WP method, which is expected to determine the right method to be applied in the performance appraisal of contract workers, and can assist the personnel department in processing the performance appraisal of contract workers. Based on the final calculation results, the SAW method and the WP method can be applied in assessing the performance of contract workers and produce the same ranking order, namely the alternative contract worker named A2 = Akmad Rosidi as the best alternative, followed by the other best alternatives A5, A1, A3, and A4. From the comparison results using the MSE (Mean Squared Error) method, the Weighted Product (WP) method produces a higher deviation value than the Simple Addative Weighting (SAW) method, with a comparison of the deviation values, namely the WP method = 228679.4811, while the SAW method = 227926, 7694. So, the Weighted Product (WP) method can be recommended in assessing the performance of contract workers at the Regional Secretariat of East Kotawaringin Regency.